Influence of thermal oxidation and maleinized liquid polybutadiene on dynamic and static performance of short aramid fiber‐reinforced carbon black‐ethylene propylene diene monomer composites. Issue 5 (18th January 2020) - Yang, Bo; Li, Peng; Luo, Zhu; Zhong, Jincheng; Yin, Lianpeng
Abstract: Short aramid fiber (AF)‐reinforced rubber composites (SFRRs) possess better mechanical performance than carbon black‐filled rubber in many respects. However, the performance of an SFRR depends on interfacial adhesion to a large extent. In this article, AF was treated by thermal oxidation and then used to prepare AF‐reinforced carbon black‐ethylene propylene diene monomer (CB‐EPDM) composites in the presence of maleinized liquid polybutadiene rubber as the compatibilizer. The interfacial adhesion between the AF and matrix was evaluated by means of the relative debonding energy (RDE), and the corresponding dynamic and static performance was studied. The interfacial adhesion could be improved by a combination of fiber surface treatment and rubber compatibility, and the RDE was increased. Compared with those of the unmodified AF‐reinforced CB‐EPDM, the tensile moduli at 100% and 300% elongation and the tear strength increased by 27.4%, 16.7%, and 22.9%, respectively, and the stress‐controlled fatigue life of the notched sample increased by 140%. The results showed that the RDE decreased gradually with increasing average deformation after strain‐controlled fatigue for 30 000 cycles, and the RDE remained at a higher level in the AF‐reinforced CB‐EPDM when better interfacial adhesion was formed.